2013
DOI: 10.3319/tao.2013.06.18.01(t)
|View full text |Cite
|
Sign up to set email alerts
|

A New Velocity Field from a Dense GPS Array in the Southernmost Longitudinal Valley, Southeastern Taiwan

Abstract: In the southernmost Longitudinal Valley (LV), Taiwan, we analyzed a dense GPS array composed of 10 continuous stations and 86 campaign-mode stations. By removing the effects of the four major earthquakes (one regional and three local) occurred during the 1992 -2010 observation period, we derived a new horizontal velocity field in this area, which then allows better locating the surface traces of the major active faults, including the Longitudinal Valley Fault (LVF) system and the Central Range Fault, and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…12). Indeed, the GPS interseismic horizontal displacements favor the latter scenario (Chen et al 2011). A recent study taken from bathymetric geomorphic features also suggests a sharp E-W turn of the LVF in the offshore area east of Taitung (O'hara et al 2011).…”
Section: Vertical Velocity Field: Combination Of Leveling and Gpsmentioning
confidence: 93%
“…12). Indeed, the GPS interseismic horizontal displacements favor the latter scenario (Chen et al 2011). A recent study taken from bathymetric geomorphic features also suggests a sharp E-W turn of the LVF in the offshore area east of Taitung (O'hara et al 2011).…”
Section: Vertical Velocity Field: Combination Of Leveling and Gpsmentioning
confidence: 93%
“…One major advantage of singlefrequency GPS is that the cost of hardware is much 1 Velocity field of the near-fault GPS array in the Taitung area. The left graph shows the vertical velocities (Chen et al, 2012) and the right graph presents the horizontal velocities relative to the ITRF2005 reference frame (Chen et al, 2013). Black lines represent major active faults: Chihshang Fault (1), Lichi Fault (2) Networks of L1 GPS receivers mixed with dualfrequency receivers have been previously proposed and tested in active fault zones and for volcano monitoring systems with encouraging results (Chen, 2001;Roberts, 2002;Rizos, 2002).…”
Section: Instrumentation and General Characteristicsmentioning
confidence: 92%
“…The convergence rate is about 8.2 cm/year, while one-third of horizontal shortening of about 3 cm/year is being absorbed across the southern LV (Yu et al, 1990;Yu and Kuo, 2001). Recent global positioning system (GPS) and precise levelling results from mostly campaign-mode surveys combined with 10 continuously operating reference stations (CORS) indicated that the velocity fields of horizontal and vertical components vary in different faults and in different locations in this area (Chen et al, 2012;Chen et al, 2013) (Fig. 1).…”
Section: Introductionmentioning
confidence: 97%
“…The International GPS Service final orbits and the standard antenna calibration were employed to reduce the effects of the orbit errors and the phase center biases. The GPS Lab processing mitigates the first‐order ionospheric bias by forming the double‐differenced ionosphere‐free linear combination of carrier phase observations (Bos & Spakman, 2003; Chen et al, 2013; Yu et al, 1997).…”
Section: Data Preparationmentioning
confidence: 99%
“…We obtain the continuous GPS daily data from the GPS Lab of the Academia Sinica (Chen et al, 2013) that comprises Taiwan's local networks of the Central Weather Bureau, Academia Sinica, and Central Geological Survey. The GPS data are routinely compiled, processed by means of Bernese software, and solved relative to the tectonically stable station (S01R) of Penghu off the west coast (Chang & Chao, 2014; Chen et al, 2013; Yu et al, 1997). The International GPS Service final orbits and the standard antenna calibration were employed to reduce the effects of the orbit errors and the phase center biases.…”
Section: Data Preparationmentioning
confidence: 99%